2010
DOI: 10.3233/jad-2010-1303
|View full text |Cite
|
Sign up to set email alerts
|

The Heme Degradation Pathway is a Promising Serum Biomarker Source for the Early Detection of Alzheimer's Disease

Abstract: One of the remaining challenges in Alzheimer's disease (AD) research is the establishment of biomarkers for early disease detection. As part of a prospective study spanning a period of five years, we have collected serial serum samples from cognitively normal, mild cognitively impaired (MCI), and mild AD participants, including same patient samples before and after cognitive decline. Using mass spectrometry we identified several promising leads for biomarker development, such as prosaposin, phospholipase D1, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 47 publications
2
43
0
1
Order By: Relevance
“…Potential Involvement of BACH1 in Pathogenic MechanismsFrom a disease-related point of view, our study revealed PSAP and MAPT as direct BACH1 target genes, both of which have been identified as potential biomarkers for the detection of Alzheimer disease (10,71). Also, the CLSTN1 gene was identified as BACH1 target, which encodes the Alzheimer-related cadherin-like protein calsyntenin 1.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Potential Involvement of BACH1 in Pathogenic MechanismsFrom a disease-related point of view, our study revealed PSAP and MAPT as direct BACH1 target genes, both of which have been identified as potential biomarkers for the detection of Alzheimer disease (10,71). Also, the CLSTN1 gene was identified as BACH1 target, which encodes the Alzheimer-related cadherin-like protein calsyntenin 1.…”
Section: Discussionmentioning
confidence: 66%
“…Several lines of evidence suggest the involvement of BACH1 in neurodegenerative diseases and cancer. Among other proteins involved in the heme degradation pathway, HMOX1 and the biliverdin reductases A and B were proposed as serum biomarkers for the early detection of Alzheimer disease (10). Furthermore, BACH1 expression was down-regulated by microRNAs in viral infection-associated cancerogenesis (11)(12)(13).…”
mentioning
confidence: 99%
“…Of the 15 proteins found to be significantly altered in sera from patients with mild AD compared to normal patients or patients with of mild cognitive impairment, 14 contained HO-1, biliverdin reductase A or biliverdin reductase B. This strongly implicates HO-1 as a potential biomarker for AD [57].…”
Section: Discussionmentioning
confidence: 95%
“…The loss of vessel integrity leads to microhemorrhages and microinfarcts. The hemorrhagic changes unleash a cascade of events including induction of heme oxygenase and biliverdin reductase, ultimately leading to local oxidative injury secondary to free-iron induced reactive oxygen species [10,11]. Additionally, there are perivascular T cell infiltrates in the vessels around microhemorrhages which may carry the inflammatory milieu a larger distance than would be affected by the microhemorrhage alone.…”
Section: Pathophysiologymentioning
confidence: 96%